Pengaruh Reward dan Punishment Terhadap Produktivitas Tenaga Kependidikan di Perguruan Tinggi - Rahmi, Wirda (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the effect of Reward (X1) and Punishment (X2) on the Productivity (Y) of educational staff at Higher Education Institution. The research employed a quantitative correlational approach to examine the relationships among variables. The research sample consisted of 173 respondents, who were educational staff at Higher Education Institution, selected using proportionate stratified random sampling. The research data were collected through questionnaire distribution, while data analysis was conducted using multiple linear regression analysis with the assistance of SPSS version 27. The results indicate that partially, the Reward (X1) variable has a positive and significant effect on Work Productivity (Y), as evidenced by a calculated t-value of 8.082, which is greater than the t-table value of 1.974, a significance value of 0.000 < 0.05, and a positive regression coefficient of 0.456. Furthermore, the Punishment (X2) variable also shows a positive and significant effect, indicated by a calculated t-value of 7.097 > 1.974, a significance value of 0.000 < 0.05, and a positive regression coefficient of 0.378. Simultaneously, both independent variables have a significant effect on productivity, as reflected by an F-value of 57.194, which is greater than the F-table value of 3.05, and a significance value of 0.000 < 0.05. The coefficient of determination (R²) is 0.402, indicating that 40.2% of the variation in educational staff productivity can be explained by reward and punishment, while the remaining 59.8% is influenced by other factors outside the research model, such as work motivation, work environment, leadership, and individual characteristics. These findings confirm that the implementation of a fair, consistent, and performance-based reward and punishment system plays an important role in enhancing the productivity of educational staff.